Respuesta :
Answer:
29
Step-by-step explanation:
Use the order of operations to solve:
(5+1)^2 - (12+3^2) /3
= 6^2 - (12+9) /3
= 36 - 21 /3
= 36-7
= 29
Use BEDMAS
B: Brackets ()
E: Exponents ^,
D: Division ,
M: Multiplication,
A: Addition
S: Subtraction
Explanation
(6^2)-(15^2)*3
6^2= 36
15^2= 225
36 - 225 = -189
-189*3= -63
=-63
B: Brackets ()
E: Exponents ^,
D: Division ,
M: Multiplication,
A: Addition
S: Subtraction
Explanation
(6^2)-(15^2)*3
6^2= 36
15^2= 225
36 - 225 = -189
-189*3= -63
=-63